PEMETAAN QUDRAH MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM DALAM MEMBACA DAN MENULIS AL-QUR’AN - Shobah Shofariyani Iryanti; Ari Khairurrijal Fahmi (Jurnal Pendidikan Islam, 2020)
Being able to read and write the Qur'an is an indicator of graduates of Islamic religious education study programs. However, many of the students were negligent in carrying out the obligation to read the Qur'an with quite varied reasons. Therefore, this study aims to analyze the qudrah of students in reading and writing the Qur'an, precisely in the UHAMKA Islamic religious education study program. This research uses a qualitative approach with a descriptive type. Data collection techniques used were tests and interviews. The results showed that the majority of first semester students in classes A, B, C, and D received a predicate of 49%. For the written test results showed 47% were in the category of inappropriate and less neat. The factors that are quite influential are motivation in self, school origin, and parents' encouragement. The results of this study have implications for the need for innovative formulations of learning to read and write the Qur'an for students so as to improve understanding and basic skills in reading and writing the Qur'an.